Answer:
![f^{(k)}(x)=\dfrac{17k!(-1)^k}{(x-9)^{k+1}}](https://tex.z-dn.net/?f=f%5E%7B%28k%29%7D%28x%29%3D%5Cdfrac%7B17k%21%28-1%29%5Ek%7D%7B%28x-9%29%5E%7Bk%2B1%7D%7D)
Step-by-step explanation:
The question presumes you have access to a computer algebra system. The one I have access to provided the output in the attachment. The list at the bottom is the list of the first four derivatives of f(x).
__
The derivatives alternate signs, so (-1)^k will be a factor.
The numerators start at 17 and increase by increasing factors: 2, 3, 4, indicating k! will be a factor.
The denominators have a degree that is k+1.
Putting these observations together, we can write an expression for the k-th derivative of f(x):
![\boxed{f^{(k)}(x)=\dfrac{17k!(-1)^k}{(x-9)^{k+1}}}](https://tex.z-dn.net/?f=%5Cboxed%7Bf%5E%7B%28k%29%7D%28x%29%3D%5Cdfrac%7B17k%21%28-1%29%5Ek%7D%7B%28x-9%29%5E%7Bk%2B1%7D%7D%7D)
40/100 + 50/100 = 90/100
il lui reste 10/100 ou 21 $
10 % = 21 $
100 % = 210 $
Well first you have to divide 3 by 4, which is 0.75 or 3/4
Answer:
A.
Step-by-step explanation:
the absolute value of -5 = 5.
5+8=13.
Hope this helped.
Answer:
{-2,10}
Step-by-step explanation:
x^2 - 8x = 20
Take the coefficient of x
-8
Divide by 2
-8/2 =-4
Square it
(-4)^2 =16
Add this to each side
x^2 - 8x+16 = 20+16
x^2 - 8x+16 = 36
The left hand side becomes( x + (-8/2) )^2
(x - 4)^2 = 36
Take the square root of each side
sqrt((x - 4)^2) =±sqrt( 36)
x-4 = ±6
Add 4 to each side
x-4+4 = 4±6
x = 4±6
x = 4+6 x = 4-6
x = 10 x = -2